PENGARUH PERBEDAAN PENAMBAHAN RUMPUT LAUT Eucheuma cotonii DAN GELATIN DENGAN BERBAGAI KONSENTRASI TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PERMEN JELLY RUMPUT LAUT - Chrisella, Angela; Kusumawati, Netty; Suseno, Thomas Indarto Putut (Jurnal Teknologi Pangan dan Gizi, 2015)
One of the areas aquaculture (Water Cultivation) are growing is the cultivation of seaweed, especially Eucheuma cotonii. Indonesia has the potential for seaweed cultivation but less in use of seaweed. In this research, seaweed is used as jelly candy’s gelling agent. In this reasearch, jelly candy made using sucrose, glucose syrup, water, and gel-forming material from combination of gelatin and Eucheuma cotonii seaweed. The design used Randomized Block Design with two factors, i.e. the proportion of gelatin (2% and 3%) and proportion of seaweed (3%, 4%, and 5%). The data obtained from the observations will be analyzed statistically using ANOVA (Analysis of Varians) test at α = 5% to find out the differences between treatments. If the ANOVA test results showed differences, then followed by DMRT (Duncan’s Multiple Range Test) at α = 5% to determine the treatment which gives affected. The result showed that interaction in addition of Eucheuma cotonii seaweed and gelatin with various concentration affected (less) the water content and springiness of jelly candy. Seaweed addition affected the water content of jelly candy. Gelatin addition affected (greater) hardness, chewiness, cohesiveness, and organoleptic characteristic of jelly candy.